The space-time CE/SE method for solving Maxwell's equations in time-domain - Wang, X.Y.; Chen, C.L.; Liu, Y. (IEEE Antennas and Propagation Society International Symposium 2002, 2002)
An innovative finite-volume-type numerical method named as the space-time conservation element and solution element (CE/SE) method is applied to solve time-dependent Maxwell's equations. Test problems of electromagnetic scattering and antenna radiation are solved for validation. Numerical results are presented and compared with the analytical solutions, showing very good agreement.